2003
DOI: 10.1002/bdrc.10013
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan and CD44: Strategic players for cell–matrix interactions during chondrogenesis and matrix assembly

Abstract: Embryonic induction, soluble and insoluble factors, receptors, and signal transduction are orchestrated for the morphogenesis of the cartilage elements. The interaction of cells with the extracellular matrix (ECM) may lead to altered cellular response to morphogens based on the formation of new adhesive contacts, or the uncoupling of cell-matrix interactions. Hyaluronan's influence on cell behavior, and its intimate association with cells are accomplished by a wide variety of specific binding proteins for hyal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
123
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(127 citation statements)
references
References 226 publications
(286 reference statements)
2
123
0
2
Order By: Relevance
“…One could also speculate that endogenous hyaluronidase activity differs in dependence on CD44v expression or that hyaluronidase inhibitors or other matrix components protect the deposited hyaluronan (51,52). The requirement of CD44 for pericellular matrix assembly in chondrocytes has been suggested to proceed through hyaluronan anchoring (53,54). Yet, as outlined in these overviews, a better understanding of the hyaluronan metabolism is required to further elucidate the function of CD44v in tumor matrix assembly (53,54).…”
Section: Asml Cells Secrete a Strongly Adhesive Matrix Which Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…One could also speculate that endogenous hyaluronidase activity differs in dependence on CD44v expression or that hyaluronidase inhibitors or other matrix components protect the deposited hyaluronan (51,52). The requirement of CD44 for pericellular matrix assembly in chondrocytes has been suggested to proceed through hyaluronan anchoring (53,54). Yet, as outlined in these overviews, a better understanding of the hyaluronan metabolism is required to further elucidate the function of CD44v in tumor matrix assembly (53,54).…”
Section: Asml Cells Secrete a Strongly Adhesive Matrix Which Supportmentioning
confidence: 99%
“…The requirement of CD44 for pericellular matrix assembly in chondrocytes has been suggested to proceed through hyaluronan anchoring (53,54). Yet, as outlined in these overviews, a better understanding of the hyaluronan metabolism is required to further elucidate the function of CD44v in tumor matrix assembly (53,54).…”
Section: Asml Cells Secrete a Strongly Adhesive Matrix Which Supportmentioning
confidence: 99%
“…Initially, HA is associated with the migration of sclerotomal, mesodermal, and neural crest cells that give rise to the axial skeleton, the limb skeleton, and the branchial arches, craniofacial bones, and cartilage (Solursh et al, 1979;Knudson and Toole, 1985;Perris et al, 1991). During limb bud outgrowth, a large amount of extracellular HA may facilitate cell division (Knudson, 2003). HA levels rapidly decrease at the time of condensation when cells aggregate before the formation of individual cartilage or bone elements.…”
Section: Has2 Is Expressed In Multiple Tissues Including Craniofaciamentioning
confidence: 99%
“…The high anionic charge of HyA may alter the visco-elastic properties of the pericellular matrix surrounding cells and as a result, preventing cells from adhering firmly onto scaffolds struts possibly leading to increased migration (Toole, 2001, Chen andAbatangelo, 1999). Another mechanism by which cell migration could be occurring may be a result of intracellular signalling pathways initiated by the specific interaction of MSCs and HyA through cell receptors such as integrins, CD44 and RHAMM (Receptor for Hyaluronic Acid Mediated Motility) (Toole, 2001, Chen and Abatangelo, 1999, Friedl and Bröcker, 2000, Knudson, 2003. Indeed it has been shown that inhibition of CD44 receptor resulted in MSCs with a reduced motility on HyA coated surfaces (Zhu et al 2006).…”
mentioning
confidence: 99%